599-P: CGM Reduces DKA in Young Adults with T1D - MCKEE, ALEXIS M.; AL-HAMMADI, NOOR; HINYARD, LESLIE J. (Diabetes (New York, N.Y.), 2021)
Diabetic ketoacidosis (DKA) is a preventable medical emergency with deleterious health consequences for persons with type 1 diabetes (T1D). We describe predictors of DKA in young adults with T1D, with a focus on socioeconomic status and use of technology. We performed a retrospective cohort study using the Optum® de-identified Electronic Health Record (EHR) dataset which contains data from 5 million adults (age 18 and older), distributed across the United States. We identified 2415 subjects with T1D aged 18-30 years with at least 1 year of follow-up data. Of the cohort, 71% were age 18-26 years, 46% were female, 74% were White, 15% were Black, and 11% were of unknown race. Also, 7% were Hispanic, 72% had commercial insurance and 51% were followed by Endocrinology. In this cohort, 17% of subjects were hospitalized for DKA within 12 months. Diabetes management included: 78% with no insulin pump and no CGM, 14% used an insulin pump without CGM, 4% used CGM without an insulin pump, and 4% used both CGM and insulin pump. Significant findings include: Those at increased odds of DKA include: individuals aged 18-26 years, males, Blacks and persons with governmental insurance. Notably, young adults with T1D using CGM were at lower odds of DKA, regardless of pump status. Conclusion: Use of CGM is associated with lower risk of DKA in a high-risk cohort of young adults with T1D. CGM should be considered for prevention of acute and chronic complications of diabetes in vulnerable populations.